2022
DOI: 10.3389/fncel.2022.945948
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Piezo1 in the Trigeminal Neurons and in the Axons That Innervate the Dental Pulp

Abstract: Information on the neurons and axons that express the mechanosensitive channel Piezo1 and its expression in axons innervating the dental pulp may help understand the nature of the Piezo1-mediated mechanosensation and the underlying mechanism of dentin sensitivity elicited by mechanical stimuli. For this, we here investigated the neurochemical properties of the neurons in the rat trigeminal ganglion (TG) and their axons in its sensory root that express Piezo1 and the expression of Piezo1 in the rat and human de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to analyze the presence of PIEZO1 and PIEZO2 in human teeth. However, our data did not suggest the presence of PIEZO1 or PIEZO2 in the pulp nerve fibers, as previously reported (Cho et al, 2022;Han et al, 2022;Sato et al, 2018;Won et al, 2017). The results for the periodontal ligament were consistent with those previously observed in mice (see Lukacs et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, this is the first study to analyze the presence of PIEZO1 and PIEZO2 in human teeth. However, our data did not suggest the presence of PIEZO1 or PIEZO2 in the pulp nerve fibers, as previously reported (Cho et al, 2022;Han et al, 2022;Sato et al, 2018;Won et al, 2017). The results for the periodontal ligament were consistent with those previously observed in mice (see Lukacs et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…Piezo1 is also expressed in nerve fibers within dental pulp. In the case of fibers, its expression in A was shown in 60.2% of small myelinated axons (Aδ) and 24.3% of large myelinated axons (Aβ), while in the case of fibers C its expression was noticed in 15.5% of unmyelinated axons [ 93 ]. Neurons engaged in signal transmission from dental pulp also express the Piezo2 mechanosensitive receptor.…”
Section: Importance Of Mechanical Cues In Bioengineering Of Dental Pu...mentioning
confidence: 99%
“…Although numerous studies have shown that PIEZO1 and 2 channels share the same overall architecture and domain composition, there are differences in cellular force-transmission pathways, indicating that PIEZO1 and 2 channels do not have exactly the same functional mechanism [ 73 ]. In vivo studies have demonstrated that while PIEZO1 channels are involved in mediating dental pain in models induced by high-threshold stimuli, PIEZO2 channels act as a low-threshold mechano-receptor that evokes pain in response to weak stimuli [ 74 , 75 ]. Xu et al reported that PIEZO1 and 2 channels together regulate inflammatory and reparative responses in odontoblasts in response to fluid shear stress overloading upon dentin injury, with PIEZO1 channels being more predominant in mechano-transduction through the integrin β1/Erk1 and Wnt/β-catenin signaling pathways [ 58 ].…”
Section: Dentin Mechano-sensingmentioning
confidence: 99%